Natural radioactivity levels of granites used in Turkey - Cetin, E.; Altinsoy, N.; Orgün, Y. (Oxford University Press (OUP), 2012)
Thirty granite samples commonly used in Turkey were surveyed for natural radioactivity. Concentrations of natural radionuclides in all samples were determined by gamma-ray spectroscopy with hyper-pure germanium detector. The activity concentrations measured for (226)Ra and (232)Th ranged from 0.7±0.1 to 186±1 Bq kg(-1), and from 0.5±0.1 to 249±2 Bq kg(-1), respectively. The activity concentrations obtained for (40)K varied from minimum detectable activity (0.4 Bq kg(-1)) to 1935±11 Bq kg(-1). The radium equivalent activity (Ra(eq)), the absorbed dose rate (D), the external hazard index (H(ex)) and the annual effective dose equivalent were also calculated and compared with the international recommended values. Granite samples were also analysed mineralogically. It was observed that the presence of large amount orthoclase and radiogenic accessory minerals are the sources of high activity concentration levels.
Keywords: Turkey; Potassium Radioisotopes; Radiation Dosage; Silicon Dioxide; Gamma Rays; Radiation Monitoring; Background Radiation; Humans; Uranium; Radium